Naps, night-time sleep and cognitive function among middle-aged and older people in China. - Xiuxiu Zhou; Yutang Tan; Di He; Hong Wu (PLoS ONE)
Background There is increasing interest in how sleep affects cognitive function; however, the combined impact of naps and night-time sleep on different cognitive domains is still not well understood. This study investigates the relationship between naps, night-time sleep, and cognitive function over time among middle-aged and older adults in China, as well as how this relationship may differ between rural and urban residents. Methods A total of 2,938 community residents aged 45 and older were selected from the China Health and Retirement Longitudinal Study (CHARLS, conducted in 2013, 2015, and 2018). The study examined the relationship between napping, night-time sleep, and cognitive function using fixed-effects analysis over a period of five years. Results Sleeping 6-8 hours/ night and napping for less than 30 minutes/ day were associated with better cognitive function (β = 0.383, 95% CI: 0.198, 0.567) and memory (β = 0.304, 95% CI: 0.155, 0.451) across the entire sample. In contrast, sleeping more than 8 hours/ night and napping more than 90 minutes/ day were associated with poor mental status. Specifically, sleeping 6-8 hours/ night was significantly associated with better cognitive function (β = 0.501, 95% CI: 0.252, 0.750) and memory (β = 0.372, 95% CI: 0.173, 0.572) in rural respondents. Sleeping more than 8 hours/ night was associated with poorer mental status among urban respondents (β = -0.291, 95% CI: -0.551, -0.032). Rural respondents who napped less than 90 minutes/ day had improved cognitive function. Napping for more than 90 minutes/ day was significantly correlated with cognitive function and mental status, which was primarily observed among urban respondents. Conclusions Considerable differences were observed between rural and urban areas regarding the relationship between napping, night-time sleep, and cognitive function. When designing interventions to enhance cognitive function, it's essential to take into account cultural context, geographical factors, and individual differences.